2022
DOI: 10.3390/antiox11020352
|View full text |Cite
|
Sign up to set email alerts
|

NRF2-Dependent Placental Effects Vary by Sex and Dose following Gestational Exposure to Ultrafine Particles

Abstract: Exposure to ultrafine particles (UFPs, PM0.1) during pregnancy triggers placental oxidative stress and inflammation, similar to fine PM (PM2.5). The Nrf2 gene encodes a redox-sensitive transcription factor that is a major regulator of antioxidant and anti-inflammatory responses. Disruption of NRF2 is known to substantially enhance PM2.5-driven oxidant and inflammatory responses; however, specific responses to UFP exposure, especially during critical windows of susceptibility such as pregnancy, are not fully ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…PM exposure was carried out as previously described in Behlen et al and Lau et al [ 12 , 27 , 53 ]. Mice ( n = 18 for FA; n = 18 for UFPs) were exposed from GD0.5 to 13.5 for 6 h/day in whole-body inhalation chambers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PM exposure was carried out as previously described in Behlen et al and Lau et al [ 12 , 27 , 53 ]. Mice ( n = 18 for FA; n = 18 for UFPs) were exposed from GD0.5 to 13.5 for 6 h/day in whole-body inhalation chambers.…”
Section: Methodsmentioning
confidence: 99%
“…The UFP chamber was monitored, and the flow of HEPA-filtered air adjusted accordingly to maintain particle concentrations of ~ 100 g /m 3 throughout the study. This dose was based on previously observed effects on offspring health [ 12 , 27 , 53 ]. Moreover, this dose was equivalent to a 24-h average exposure 25 g /m 3 , just under the EPA PM 2.5 regulatory level (35 g /m 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the placental malfunction associated abnormal intrauterine environment during the embryonic period not only inhibits the fetus’ development and growth but also increases the risk of diabetes, hypertension and cardiovascular diseases after birth [ 2 ]. Even though multiple risk factors are attributed to placental dysfunctions, one of them is oxidative stress [ 3 , 4 ]. It has been reported that maternal exposure to high levels of reactive oxygen species (ROS) during pregnancy impairs placental function and leads to poor outcomes in pregnancy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%